2005
DOI: 10.1002/hep.20514
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis in human hepatocytes suggests a mechanism for hepatotoxicity induced by trovafloxacin

Abstract: Idiosyncratic drug toxicity, defined as toxicity that is dose independent, host dependent, and usually cannot be predicted during preclinical or early phases of clinical trials, is a particularly confounding complication of drug development. An understanding of the mechanisms that lead to idiosyncratic liver toxicity would be extremely beneficial for the development of new compounds. We used microarray analysis on isolated human hepatocytes to understand the mechanisms underlying the idiosyncratic toxicity ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 39 publications
4
66
0
Order By: Relevance
“…Thus Liguori et al (2005) used a method of microarray analysis on isolated human hepatocytes by which they clearly distinguished between TVA and other marketed quinolone agents, and identified unique gene changes induced by TVA that are involved in mitochondrial damage, RNA processing, transcription, and inflammation, which may suggest a possible mechanism for the hepatotoxicity induced by this agent (8). Sun et al (9,10) suggested a model of a cyclopropylamine-containing system that implies oxidation of cyclopropylamine moiety to reactive ring-opened intermediates with a carbon-centered radical, which can be subsequently converted to a,b-unsaturated aldehyde.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus Liguori et al (2005) used a method of microarray analysis on isolated human hepatocytes by which they clearly distinguished between TVA and other marketed quinolone agents, and identified unique gene changes induced by TVA that are involved in mitochondrial damage, RNA processing, transcription, and inflammation, which may suggest a possible mechanism for the hepatotoxicity induced by this agent (8). Sun et al (9,10) suggested a model of a cyclopropylamine-containing system that implies oxidation of cyclopropylamine moiety to reactive ring-opened intermediates with a carbon-centered radical, which can be subsequently converted to a,b-unsaturated aldehyde.…”
mentioning
confidence: 99%
“…Recently, the possible mechanisms of TVA hepatotoxicity were discussed in several papers (8)(9)(10). Thus Liguori et al (2005) used a method of microarray analysis on isolated human hepatocytes by which they clearly distinguished between TVA and other marketed quinolone agents, and identified unique gene changes induced by TVA that are involved in mitochondrial damage, RNA processing, transcription, and inflammation, which may suggest a possible mechanism for the hepatotoxicity induced by this agent (8).…”
mentioning
confidence: 99%
“…One exception is trovafloxacin, the use of which has been restricted because of hepatic idiosyncratic drug reaction (IDR) issues (Bertino and Fish, 2000). Our laboratory has previously demonstrated that microarray analysis can distinguish trovafloxacin from other quinolones not associated with hepatic toxicity in PHH (Liguori et al, 2005). Since then, other examples of unique gene expression patterns in PHH or other culture systems from IDRcausing drugs relative to pharmacologically related compounds have been reported (Kier et al, 2004;Guo et al, 2006).…”
mentioning
confidence: 99%
“…Moreover, human hepatocytes are subject to various stimuli such as exposure to a wide assortment of drugs, environmental influences, disease, diet, natural hormones, alcohol, tobacco, trauma, and genetic variation, among other factors that contribute to experimental variability. Indeed, differences in gene expression have been observed across donors of human hepatocytes (LeCluyse, 2001;Liguori et al, 2005). Lastly, the sporadic availability and significant cost associated with the use of human hepatocytes must be considered.…”
mentioning
confidence: 99%
“…Several drugs have been withdrawn from the market due to the severe adverse effects in patients [24][25][26]. Most of these drugs have shown potential to cause toxicity in healthy organs such as hepatotoxicity and nephrotoxicity [27][28][29]. On the other hand, camel's milk (CM) is an excellent source of wellbalanced nutrients and serves as the main source of food.…”
Section: Safety Profilementioning
confidence: 99%